COMMUNITY PARTICIPATION IN FAMILY PLANNING (KB) PROGRAM FOR YOUNG COUPLES IN SIDOARJO REGENCY - Irianto, Heru; Nurany, Fierda; Indriani, Eva Oktavia (DIA: Jurnal Administrasi Publik, 2025)
One way to reduce the birth rate is community participation in family planning (KB) programs. To control population growth and improve family welfare, this program is very important. By actively participating, people better understand the importance of family planning (KB) programs and are better able to take advantage of the services provided by the government. The purpose of this study was to determine the type of community participation shown by young couples in running family planning (KB) programs, what factors hinder community participation in family planning (KB) programs, and how to increase community participation in family planning (KB) programs. in the Sidoarjo area. Qualitative methods are used. Information is gathered through interviews and documentation. Data analysis involves data reduction, data submission, and conclusions. The results of research and discussion showed that young couples in Sidoarjo Regency were quite active in participating in family planning (KB) programs. Factors that hinder community participation include cultural factors, partner beliefs, and health factors. Therefore, it is necessary to increase community participation to be more active in participating in family planning programs. About how important family planning (KB) programs are for society, especially young couples, because it gives them more time to prepare for the future of their families